Perilaku Hidup Bersih dan Sehat Pondok Pesantren Al-Ishlahul Ma’arif Pada Masa New Normal - Kartika Risfianty, Dwi; Indrawati, Indrawati; Heniati Santosa, Farah; Bahri, Samsul; Samsuriadi, Samsuriadi; Wulandari, Wulandari; Sulhiyawati, Sulhiyawati (Rengganis Jurnal Pengabdian Masyarakat, 2021)
Covid-19 is a respiratory tract infection that is transmitted through coughing and sneezing. Covid-19 is characterized by the appearance of flu symptoms, cough, fever, respiratory problems and even death. The community in the Al-Ishlahul Ma'arif Islamic boarding school in Kediri, West Lombok, still looks unfamiliar with wearing masks when inside and outside the cottage environment. The purpose of this community service is to empower the community in using masks and implementing a clean and healthy lifestyle. The service method is in the form of donations of masks, vitamins and disinfectants as well as presentation on how to use them orally in addition to providing information related to clean and healthy living behavior in an effort to prevent COVID-19. The results obtained are that all residents of the cottage have received masks, vitamins, and disinfectants. In addition, all residents of the cottage get useful information related to clean and healthy living. Thus, the community in the Al-Ishlahul Ma'arif Islamic boarding school in Kediri, West Lombok, can finally consume vitamins, use masks, use disinfectants, and apply clean and healthy living behaviors